PENGEMBANGAN MEDIA POWER POINT SEBAGAI BAHAN AJAR PENDUKUNG MATA PELAJARAN BAHASA JEPANG KELAS X DI SMA NEGERI 1 MINAS KABUPATEN SIAK - Yeni, Hutri Yeni; Widiati, Sri Wahyu Widiati Wahyu; Basri, Merri Silvia Basri Silvia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is about the development of power point as supporting teaching media of Japanese subject in SMAN 1 Minas, kabupaten Siak. This research aims to know whether power point as supporting teaching media of Japanese subject  in SMAN 1 Minas, kabupaten Siak is appropriate with standard of experts or validator, so it is suitably used in the real learning process. This research uses SCL theory and research and development method. This research uses questioner as data accumulation technique. The result of this research is power point supporting teaching media. Keywords : Development, Power Point, Teaching Media